centrocortin RNA localization to centrosomes is regulated by FMRP and facilitates error-free mitosis - Ryder, Pearl V. (J Cell Biol, 2020)
Centrosomes are microtubule-organizing centers required for error-free mitosis and embryonic development. The microtubule-nucleating activity of centrosomes is conferred by the pericentriolar material (PCM), a composite of numerous proteins subject to cell cycle–dependent oscillations in levels and organization. In diverse cell types, mRNAs localize to centrosomes and may contribute to changes in PCM abundance. Here, we investigate the regulation of mRNA localization to centrosomes in the rapidly cycling Drosophila melanogaster embryo. We find that RNA localization to centrosomes is regulated during the cell cycle and developmentally. We identify a novel role for the fragile-X mental retardation protein in the posttranscriptional regulation of a model centrosomal mRNA, centrocortin (cen). Further, mistargeting cen mRNA is sufficient to alter cognate protein localization to centrosomes and impair spindle morphogenesis and genome stability.